Uma avaliação da expansão dos cursos de graduação da Universidade Federal do Ceará: uma análise do periodo de 2008 A 2011 - Reis, Ivonilde Mendes Falcão (2014)
The present research assessed the success rate mark performance on graduation courses offered by UFC and its relation with characteristic variables on these same courses, as for the number of registered students, number of graduation courses per academic unit, number of graduate students and the number of instructors in each academic unit, accounting the academic units present in UFC from 2008 to 2011. Concerning the estimate results according to the econometric model, chart 7, it could be stated that the estimated coefficients for the variables, DIPLOMA, INSTRUCTOR AND REGISTER resulted statistically significant at the level of 5%. Further, the variant GRADUATION COURSE was statistically significant at the level of 10%. The variant REGISTER had a weak impact over the dependent rate success variant (port. “TXSUC”) and the variant COURSE, as well as the variant REGISTER, showed a negative impact over the Success Rate. Furthermore, the variants DIPLOMA and INSTRUCTOR showed positive coefficients.